1997
DOI: 10.1159/000461990
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Genotyping of Human Platelet Antigens by Hot Start Sequence- Specific Polymerase Chain Reaction with DNA Polymerase AmpliTaq Gold

Abstract: Objectives: Human platelet alloantigen (HPA) typing has potential clinical relevance in a variety of contexts. We can improve methods for HPA genotyping by complementing our knowledge of the DNA sequence polymorphisms of HPA genes and experience with various DNA-based HPA typing techniques. Methods: A newly available DNA polymerase, AmpliTaq Gold (Perkin Elmer), provided in an inactive state and activated by heat, makes it possible to perform a hot start polymerase chain reaction (PCR) in order to prevent nons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 14 publications
3
29
1
Order By: Relevance
“…Until recently, only al-ternative strategies such as ligase chain reactions [9] offered adequate specificity. Two groups [7,8] have recently demonstrated that a hot-start technique may enhance both the specificity and the efficiency of sequence-specific PCR for HPA typing. The present study demonstrates that the specificity of PCR catalyzed by AmpliTaq Gold TM suffices for reliable HPA-1 genotyping by ELISA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until recently, only al-ternative strategies such as ligase chain reactions [9] offered adequate specificity. Two groups [7,8] have recently demonstrated that a hot-start technique may enhance both the specificity and the efficiency of sequence-specific PCR for HPA typing. The present study demonstrates that the specificity of PCR catalyzed by AmpliTaq Gold TM suffices for reliable HPA-1 genotyping by ELISA.…”
Section: Discussionmentioning
confidence: 99%
“…This amino acid dimorphism is due to a single base pair substitution in the coding gene (C^T sub stitution at nucleotide position 196 of the coding DNA) [1]. Polymerase chain reactions (PCR) with allele-specific primers have been established as a valid method for HPA genotyping [2][3][4][5][6][7][8], This method still requires identification of the amplificates by gel-electrophoretic analysis of the products from two reactions per DNA sample essentially limiting the sample throughput.…”
Section: Introductionmentioning
confidence: 99%
“…Each data entry (bar) represents the mean and standard deviation for the number of studies indicated in parentheses. References: White, 36,[188][189][190][191][192][193][194][195][196][197][198][199][200][201][202][203]220 Southeast Asian, 36 Asian, 36,189,190,204,205,[207][208][209][210][211][212][213]215 Central African, 36 North African, 36,216,217 black American, [188][189][190]203,220 Amerindian, 188,189,218 Native American, 220 and Aboriginal. 202,219…”
Section: Isoantibodies In Bernard-soulier Syndromementioning
confidence: 99%
“…Each data entry (bar) represents the mean and standard deviation for the number of studies indicated in parentheses. References: White,36,[188][189][190][191][192][193][194][195][196][197][198][199][200][201][202][203] Southeast Asian,…”
mentioning
confidence: 99%
“…To obtain a higher level of specificity while simultaneously genotyping for human platelet antigens (HPA) (3) and for HLA class I and class 11, we employed a DNA polymerase AmpliTaq Gold (Perkin Elmer). As described by the manufacturer, this polymerase is provided in an inactive state and becomes activated when heated.…”
mentioning
confidence: 99%